Drie nuwe verklaringsopsies in die Jakobusbrief (Jak 2:1; 4:5; 5:6) - Pretorius, E. a. C. (Hervormde teologiese studies, 1988)
New options in the understanding of the Epistle of James(Js 2:1; 4:5; 5:6) New methods of interpretation occasionally lead to new options in the understanding of texts. In the case of the Epistle of James, the interpretation has until recently stood under the spell of the 'comparative' method of Dibelius. Greater emphasis on internal cohesion in the text recently led to the proposal of the following translations: James 2:1: '... surely, you do not have the faith in our Lord ... on account of favouritism?' James 4:5: 'Do you think Scripture speaks in vain? Should the spirit which He made to dwell in us desire (the world) with envy?' James 5:6 'You judge and murder the innocent. Will He (God, cf 4:6) not resist you?'